2002
DOI: 10.1590/s0066-782x2002000200007
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Modulation of the Heart in Systemic Arterial Hypertension

Abstract: Variability in heart rate was a valuable instrument for analyzing autonomic modulation of the heart in arterial hypertension. The autonomic system undergoes significant losses in cardio-modulatory capacity, more evident in subjects between 40 and 59 years old. In those over 60 years old, reduced variability in heart rate imposed by aging was not significantly influenced by the presence of systemic arterial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The software used to process the data was the Biopotentials Captation System, developed by Barbosa in 1997, 31 which allows the examiner to eliminate QRS complexes with artefacts, to measure the HRV in the time and frequency domains. The method was validated for reproducibility in the same publication 31 and has been used in other studies 32,33 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The software used to process the data was the Biopotentials Captation System, developed by Barbosa in 1997, 31 which allows the examiner to eliminate QRS complexes with artefacts, to measure the HRV in the time and frequency domains. The method was validated for reproducibility in the same publication 31 and has been used in other studies 32,33 …”
Section: Methodsmentioning
confidence: 99%
“…The method was validated for reproducibility in the same publication 31 and has been used in other studies. 32,33 After 5 min of rest, the patients underwent the respiratory sinus arrhythmia (RSA) manoeuvre, with a controlled respiratory rate of 12 incursions per min (over 2 min), to provoke a vagal response. 34,35 They remained supine until 20th min, when the bed was tilted to 70 degrees, and a sympathetic response was expected.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that there is a decrease in HRV with advancing age [2][3][4][5][6] and that this reduction is associated with the emergence or worsening of cardiovascular disease, increasing the risk of death from all causes [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Maind et al, [ 27 ] the systolic blood pressure before pursed-lip breathing was 144.32 ± 10.80 and after pursed-lip breathing 149.89 ± 8.08 (P < 0.015) and diastolic blood pressure changed from 77.35 ± 5.45 to 77.62 ± 5.47, respectively that is consistent with this study. Variation in BP can be due to changes in the chest compression due to respiratory movements, which compensate for the increase or decrease in systolic blood pressure fluctuations [ 5 ] [ 28 ]. The number and rhythm of respiration not only affects the respiratory system but also has direct effects on the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%